Immunotherapy for Metastatic Non-Small Cell Lung Cancer: Real-World Data from an Academic Central and Eastern European Center. (2nd August 2021) - Ivanović, Marija; Knez, Lea; Herzog, Ana; Kovačević, Mile; Cufer, Tanja
Abstract : Background: Immunotherapy with immune checkpoint inhibitors (ICIs) recently became the standard treatment for patients with advanced non-small cell lung cancer (NSCLC). Here, we present the first results of a real-world observational study on the effectiveness of ICI monotherapy in patients with advanced NSCLC treated at a single academic center in a Central and Eastern European (CEE) country. Materials and Methods: Overall, 66 consecutive patients with advanced NSCLC treated with ICIs in everyday clinical practice, either with first-line pembrolizumab (26 patients) or second-line atezolizumab, nivolumab, or pembrolizumab (40 patients), from August 2015 to November 2018, were included. All data were retrieved from a hospital lung cancer registry, in which the data is collected prospectively. Results: Included patients had a median age of 64 years, most were male (55%), 6% were in performance status ≥2, and 18% had controlled central nervous system metastases at baseline. In first-line, the median progression-free survival (mPFS) was 9.3 months, while the median overall survival (mOS) was not reached. The 1-year overall survival (OS) was 62%. In second-line, the mPFS and mOS were 3.5 months and 9.9 months, respectively, with a 1-year OS of 35%. In the overall population, adverse events of any grade were recorded in 79% of patients and of severe grade (3–4) in 12% of patients. Conclusion: The first real-world outcomes of NSCLC immunotherapy from a CEE country suggest comparable effectiveness to those observed in clinical trials and other real-world series, mainly coming from North America and Western European countries. Further data to inform on the real-world effectiveness of immunotherapy worldwide are needed. Implications for Practice: Immunotherapy is a standard treatment of advanced non-small cell lung cancer (NSCLC). The real-world data on immunotherapy are still limited. This article presents the first data on the effectiveness of mono-immunotherapy with immune checkpoint inhibitors for patients with advanced NSCLC treated at a single academic center in a Central and Eastern European country. The survival rates and toxicity are comparable to those achieved in randomized clinical trials and other real-world series, coming mainly from North American and Western European countries. There is a pressing need to gather further data on the effectiveness of immunotherapy in everyday practice worldwide. Abstract : Immunotherapy has become the standard treatment for advanced non-small cell lung cancer (NSCLC). This article presents the first real-world results on the effectiveness of immune checkpoint inhibitor treatment for advanced NSCLC from a single academic center from Central and Eastern European country.